Pengaruh Tempat Tumbuh Terhadap Kadar Alfa Tokoferol Pada Buah Mengkudu (Morinda Citrifolia L.): The Effect of Location on Alfa Tocopherol Levels in Noni Fruit (Morinda Citrifolia L.) - Sri Gustini Husein; Wiwin Winingsih; Nurdianti Nurdianti; Achmad Zainuddin (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Alpha tocopherol (?-tocopherol) contained in noni fruit (Morinda citrifolia L.) is one of the antioxidants that contribute to pharmacological effects. The noni plant is a tropical plant that has broad growing requirements, so that this plant can grow anywhere. Although easy to find, the environmental conditions where noni grows will have an influence on the amount of ?-tocopherol it contains, one of which is the difference in where it grows. The purpose of this study was to determine the levels of ?-tocopherol in the n-hexane fraction of noni fruit, which grows in three different growing places. Analysis for ?-tocopherol by High Performance Liquid Chromatography (HPLC) with a validated analytical method. The results of system suitability test HPLC System for ?- tocopherol analysis were as follows isocratic elution system of a mobile phase 100% methanol, uv detector at a wavelength of 292 nm using the column C18 (150 ? 4, 6mm, 5?m) flow rate of 1 ml / min. The method had linear concentration range from 1-25 ppm, with R2 0.9967. The accuracy of this method that represented by recovery was 98.02-99.252%. The precision of this method that expressed by Relative Standard Deviation (RSD) was 0.262% and has good specificity. From the analysis, it was found that the content of ?-tocopherol in noni fruit was different and had a positive correlation with the height where it grew, namely in Pameungpeuk (18 m asl) of 0.0316%; Kiaracondong (173 m asl) of 0.0637%; and Lembang (1200 m asl) at 1.0853%.